Marine Algae Polysaccharides as Basis for Wound Dressings, Drug Delivery, and Tissue Engineering: A Review - Tatyana A. Kuznetsova; Boris G. Andryukov; Natalia N. Besednova; Tatyana S. Zaporozhets; Andrey V. Kalinin (Journal of Marine Science and Engineering, 2020)
The present review considers the physicochemical and biological properties of polysaccharides (PS) from brown, red, and green algae (alginates, fucoidans, carrageenans, and ulvans) used in the latest technologies of regenerative medicine (tissue engineering, modulation of the drug delivery system, and the design of wound dressing materials). Information on various types of modern biodegradable and biocompatible PS-based wound dressings (membranes, foams, hydrogels, nanofibers, and sponges) is provided; the results of experimental and clinical trials of some dressing materials in the treatment of wounds of various origins are analyzed. Special attention is paid to the ability of PS to form hydrogels, as hydrogel dressings meet the basic requirements set out for a perfect wound dressing. The current trends in the development of new-generation PS-based materials for designing drug delivery systems and various tissue-engineering scaffolds, which makes it possible to create human-specific tissues and develop target-oriented and personalized regenerative medicine products, are also discussed.